Pengaruh matriks kapsul terhadap perkecambahan benih sintetik teh (Camellia sinensis L.) Effect of capsule matrix on germination of synthetic seeds of tea (Camellia sinensis L.) - . SUMARYONO; Rizka T SAPTARI (E-Journal Menara Perkebunan, 2015)
Abstract         Synthetic seed technology has been developed to combine the practical use of ordinary seeds and clonal plant materials. Single somatic embryos of tea (Camellia sinensis L.) clone GMB 9 were encap-sulated using sodium alginate and CaCl2 at different concentrations to produce synthetic seeds.  Encapsulating matrices with and without somatic embryos were made of WP medium and 20 g/L sucrose with   1, 2 or 3%  sodium alginate and 50 or 100 mM CaCl2. Encapsulating matrices without somatic embryos were then tested its physical characteristics, whereas the capsules with somatic embryos were observed its germination rate and secondary embryo formation every week up to six weeks. The results showed that the concentrations of sodium alginate and CaCl2 were affected significantly the physical characteristics of encap-sulating matrix produced. The sufficient level of hardness and highest germination rate was obtained from 2% sodium alginate and 50 mM CaCl2. Sodium alginate at 1% or less produced soft, leaky and oval encapsulating matrices which were not suitable for synthetic seeds. Sodium alginate 3% and 100 mM CaCl2  produced rounded and very hard encapsulating matrices and inhibited the germination of somatic embryos. Germination rates of tea synthetic seeds and somatic embryos without encapsulation were 5 to 20% after six weeks. Abstrak         Teknologi benih sintetik dikembangkan untuk memadukan kepraktisan penggunaan benih biasa dengan bahan tanam klonal. Embrio somatik tunggal dari tanaman teh (Camellia sinensis L.) klon GMB 9 dienkapsulasi menggunakan natrium alginat   dan CaCl2 untuk membuat benih sintetik. Matriks kapsul dengan dan tanpa embrio somatik dibuat dari medium WP dengan sukrosa 20 g/L dicampur dengan natrium alginat 1, 2, atau 3% dan CaCl2 50  atau 100 mM.  Matriks  kapsul  tanpa embrio somatik kemudian diuji sifat fisiknya, sedangkan matriks kapsul dengan embrio somatik diamati daya kecambah dan pembentukan embrio somatik sekunder setiap minggu sampai dengan enam minggu. Hasil penelitian menunjukkan bahwa konsentrasi natrium alginat dan CaCl2 sangat berpengaruh terhadap sifat fisik matriks kapsul yang dihasilkan. Tingkat kekerasan yang memadai dan menghasilkan persentase perkecambahan yang tinggi diperoleh dengan alginat 2% dan CaCl2 50 mM. Natrium alginat pada konsentrasi 1% atau kurang menghasilkan matriks kapsul yang  lunak, mudah bocor dan berbentuk lonjong sehingga tidak sesuai untuk benih sintetik. Natrium alginat konsentrasi 3% pada larutan CaCl2 100 mM menghasilkan benih sintetik yang bulat, sangat keras dan menghambat perkecambahan embrio somatik teh.  Daya kecambah benih sintetik dan embrio somatik teh tanpa enkapsulasi berkisar  5 - 20% setelah enam minggu.